Performa Produksi Telur Turunan Pertama (F1) Persilangan Ayam Arab dan Ayam Kampung yang Diberi Ransum dengan Level Protein Berbeda - Husmaini Husmaini; Sabrina Sabrina (Universitas Andalas, 2006)
An experiment has been conducted to study the effect of diets with different level of protein on the production performance of offspring (F1) crossbred between arab and kampung chicken. Fifty four crossbreed hens of 20 weeks of age were used in the experiment. The hens were divided into 3 feeding groups, each 6 x 3 heads. Treatment diets were formulated in three different levels of protein: 15, 17 and 19 %. The diets which an average energy content of 2850 kcal/kg were offered for 8 weeks. Variable observed included: feed intake, hen day egg production, FCR, egg weight and color index of yellow egg. The data were statistically analyzed by variance analysis in completely block design with 3 treatments and 6 replicates. The results indicated the protein level had significant effect on all variables. Diet with 19 % crude protein gave the best performance.